USING INSTAGRAM AS A TOOL FOR ONLINE PEER-REVIEW ACTIVITY IN WRITING DESCRIPTIVE TEXT FOR SENIOR HIGH SCHOOL STUDENTS - Jepri Bobby Sirait; Leni Marlina (Journal of English Language Teaching, 2018)
This paper is purposed to explain the procedure in using Instagram for online peer-review activity toopl in writing descriptive text for senior high school students (SMA). Instagram is chosen as the media because instagram is one of social media that is recently popular among people, expecially the teenagers. Thus, instagram is developed as the tool for online peer-review activity in writing descriptive text. There are some peer-review stages that will be applied in this paper namely self-, pair and group-revising. The instagram will be used in the group-revising stage. In using instagram as the tool, the students will give their writing to an admin, and the admin will post it on the class account. Thus, other students will give their comments then. There are some advantages in using instagram as a tool for online peer-review activity in writing descriptive text. The first advantage is using this technique will motivate students in writing. Second, using instagram will give convenient and easy to use. Then, using instagram needs less paper. After that, using instagram is more flexible in time. Using instagram allows for multimedia interaction. Last, the students will take responsibility for their works.